2023
DOI: 10.3390/ma16186148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repressing Lithium Disilicate Glass Ceramics on The Shear Bond Strength of Resin Cements

Tariq S. Abu Haimed,
Saeed J. Alzahrani,
Esraa A. Attar
et al.

Abstract: The aim of this study was to investigate the effect of repeated pressing of lithium disilicate ceramic on the shear bond strength (SBS) of three types of resin cement. Methodology: A lithium disilicate ceramic (IPS e.max® Press) was first heat-pressed to form rectangular disk specimens. Then, leftovers were used for the second and third presses. A total of 90 specimens were prepared and separated, according to the number of pressing cycles, into three groups: 1st, 2nd, and 3rd presses (n = 30). Each group was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A study by Abu Haimed et al [12], stated that there was a statistical difference in the bond strength with different resin cements against the pressable lithium disilicate glass ceramics regardless of the number of pressing cycles. The type of resin cements affected the shear bond strength of the pressable ceramics, which is in contradiction to the current study where there was no statistically significant difference found between the bond strength of the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Abu Haimed et al [12], stated that there was a statistical difference in the bond strength with different resin cements against the pressable lithium disilicate glass ceramics regardless of the number of pressing cycles. The type of resin cements affected the shear bond strength of the pressable ceramics, which is in contradiction to the current study where there was no statistically significant difference found between the bond strength of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical tests show that the binding around porcelain veneer borders weakens, especially in the cervical areas of the anterior teeth. Not only may such debonding cause visual problems, but it could also cause secondary caries, post-operative sensitivity, and plaque development [10][11][12]. Furthermore, many patients seek treatment with veneers for periodontal diseases, which can lead to gingival recessions and exposed root surfaces in the area of the anterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium disilicate crystals (LD), as a widely used glass ceramic material, are inserted into a ceramic matrix consisting of quartz, lithium dioxide, alumina, phosphorus oxide, potassium oxide, and other oxide substitutes [1]. It is known to be one of the best versatile metal-free alternatives among the all-ceramic types, being applied both for anterior and posterior purposes [2].…”
Section: Introductionmentioning
confidence: 99%